1989
DOI: 10.1164/ajrccm/140.5.1290
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Constant Positive Airway Pressure Inhibits the Swallowing Reflex

Abstract: The effects of constant positive airway pressure applied via a nose mask through the nares (nasal CPAP) on the swallowing reflex were studied in eight adult humans. The swallowing reflex was induced by bolus injections of a small amount of distilled water (0.5 ml) into the pharynx at four different values of endexpiratory airway pressure (0,5,10, and 15 cm H2O CPAP) or by continuous infusion of water (3 ml/min) at two different values of endexpiratory airway pressure (0 and 15 cm H2O CPAP). The latency of resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 3 publications
0
30
0
Order By: Relevance
“…Concerning this possibility, it has been shown that nasal continuous positive airway pressure (CPAP) or negative extrathoracic pressure applied in normal adult humans decreases the frequency of repeated swallows [6,7]. Furthermore, our recent study showed that hyperpnea decreased and breath-holding increased the frequency of repeated swallows [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning this possibility, it has been shown that nasal continuous positive airway pressure (CPAP) or negative extrathoracic pressure applied in normal adult humans decreases the frequency of repeated swallows [6,7]. Furthermore, our recent study showed that hyperpnea decreased and breath-holding increased the frequency of repeated swallows [8].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the first possibility, there are several reports [5][6][7][8] to support the idea that the vagally mediated reflexes such as lung/pulmonary reflexes and upper airway reflexes play an important role in the control of the swallowing reflex. On the other hand, no substantial evidence to support possibility (2) above has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nasal CPAP has been previously shown to inhibit waterinduced swallowing in conscious adult humans (12) and spontaneous NNS in newborn lambs during QS (19). However, the precise reflex mechanism(s) by which swallowing is inhibited by nasal CPAP remains unclear.…”
Section: Effect Of Positive Airway Pressure On Nns Frequencymentioning
confidence: 99%
“…We recently reported that a nasal CPAP of 6 cmH 2 O inhibits spontaneous NNS in newborn lambs during quiet sleep (QS) (19). Although such effects were previously reported for waterinduced swallowing in conscious adult humans (12), the precise mechanism by which swallowing is inhibited by nasal CPAP remains unclear. Recent findings suggest it may be mediated by mechanoreceptors in the upper airways or by bronchopulmonary slowly adapting stretch receptors (SARs).…”
mentioning
confidence: 96%
“…However, while there are few reports of adverse events in the literature, they relate to barotrauma [75] and loss of airway protection [76]. The use of CPAP in hypercapnia and/or hypoventilation may be inappropriate as tidal volume and minute ventilation are uncontrolled [74].…”
Section: Precautions With Continuous Positive Airway Pressure Treatmentmentioning
confidence: 99%